2021
DOI: 10.1111/acv.12668
|View full text |Cite
|
Sign up to set email alerts
|

There will be conflict – agricultural landscapes are prime, rather than marginal, habitats for Asian elephants

Abstract: Misconceptions about species’ ecological preferences compromise conservation efforts. Whenever people and elephants share landscapes, human–elephant conflicts (HEC) occur in the form of crop raiding, elephant attacks on people and retaliatory actions from people on elephants. HEC is considered the main threat to the endangered Asian elephant Elephas maximus. Much of HEC mitigation in Asia is based on rescuing elephants from conflict areas and returning them to nature, for example, by means of ‘problem elephant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 53 publications
0
31
0
Order By: Relevance
“…We computed land-use metrics separately in 2000 and 2020, based on the global land use data product GlobeLand30 (Chen et al 2014), using the sampling strategy of a moving window at 5 radii in FRAGSTATS version 4.2.1 (McGarigal et al 2012). We computed metrics at the class level (each land-use type) for 4 potentially important land uses: mixed forest, grassland, cropland, and buildings (Liu et al 2018, Neupane et al 2019, de la Torre et al 2021.…”
Section: Methodsmentioning
confidence: 99%
“…We computed land-use metrics separately in 2000 and 2020, based on the global land use data product GlobeLand30 (Chen et al 2014), using the sampling strategy of a moving window at 5 radii in FRAGSTATS version 4.2.1 (McGarigal et al 2012). We computed metrics at the class level (each land-use type) for 4 potentially important land uses: mixed forest, grassland, cropland, and buildings (Liu et al 2018, Neupane et al 2019, de la Torre et al 2021.…”
Section: Methodsmentioning
confidence: 99%
“…Such fragmented habitats cause elephants to come into closer proximity and greater contact with human society as elephants seek to fulfill their nutritional, ecological and behavioral needs (Sukumar, 1990). This overlap in the space use between people and elephants lead to more frequent conflict (Wilson et al, 2015;de la Torre et al, 2021). Although past studies have analyzed spatial variation of HEC, conceptual obstacles still exist due to the complex nature of the relationship between HEC and its occurrence in a specific spatial context.…”
Section: Discussionmentioning
confidence: 99%
“…The new estimate suggests a need to carefully consider any population impacts, systematically identify areas where elephants can be translocated, and develop translocation guidelines. Also, several studies have suggested that translocation is not an effective or a long-term solution (Fernando et al 2012, de la Torre et al 2021, and small populations may suffer a very high relative extinction risk even at a low removal (translocation) rate (Saaban et al 2020).…”
Section: Elephant Translocationsmentioning
confidence: 99%